Evaluation of Chitosan-Microcrystalline Cellulose Blends as Direct Compression Excipients - Olorunsola, Emmanuel O. (J Drug Deliv, 2017)
This study was aimed at evaluating chitosan-microcrystalline cellulose blends as direct compression excipients. Crab shell chitosan, α-lactose monohydrate, and microcrystalline cellulose powders were characterized. Blends of the microcrystalline cellulose and chitosan in ratios 9 : 1, 4 : 1, 2 : 1, and 1 : 1 as direct compression excipients were made to constitute 60% of metronidazole tablets. Similar tablets containing blends of the microcrystalline cellulose and α-lactose monohydrate as well as those containing pure microcrystalline cellulose were also produced. The compact density, tensile strength, porosity, disintegration time, and dissolution rate of tablets were determined. Chitosan had higher moisture content (7.66%) and higher moisture sorption capacity (1.33%) compared to microcrystalline cellulose and lactose. It also showed better flow properties (Carr's index of 18.9% and Hausner's ratio of 1.23). Compact density of tablets increased but tensile strength decreased with increase in the proportion of chitosan in the binary mixtures. In contrast to lactose, the disintegration time increased and the dissolution rate decreased with increase in the proportion of chitosan. This study has shown that chitosan promotes flowability of powder mix and rapid disintegration of tablet. However, incorporation of equal proportions of microcrystalline cellulose and chitosan leads to production of extended-release tablet. Therefore, chitosan promotes tablet disintegration at low concentration and enables extended-release at higher concentration.